Alcohol-containing leakage-proof paste as well as preparation method and application thereof

By using the combination of PVM/MA copolymer butyl ester, alcohol, guar bean gum and other ingredients in the leakproof paste, the leakproof paste has solved the problems of poor corrosion resistance, insufficient support, strong skin irritation or inconvenient shape, achieving higher corrosion resistance and support performance, and reducing skin irritation.

CN119524190APending Publication Date: 2025-02-28ZHENDE MEDICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411736780.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

Smart Images

  • Figure CN119524190A_ABST
    Figure CN119524190A_ABST
Patent Text Reader

Abstract

The invention discloses alcohol-containing leakage-proof paste as well as a preparation method and application thereof, and belongs to the technical field of surgical article materials. According to the invention, PVM / MA copolymer butyl ester, alcohol, guar gum, a first thickening agent and a second thickening agent are used as raw materials, and the ratio of the raw materials is optimized, so that the alcohol-containing leakproof paste is prepared. The alcohol-containing leakproof cream has relatively weak irritation to skin, is convenient to shape, and has relatively good thermal stability, supporting performance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surgical supplies materials, in particular to an alcohol-containing anti-leakage ointment and a preparation method and application thereof. Background Art

[0002] A stoma is an exposed opening formed by leading one end of the intestine or urethra to the surface of the body, and is used to treat diseases of the digestive system or urinary system. Since there is no sphincter at the stoma, the patient cannot control defecation and needs to wear a stoma bag to collect secretions and excrement. In stoma care, leak-proof ointment is an important auxiliary product. Leak-proof ointment is used to apply to irregular skin surfaces to fill wrinkles and depressions to ensure a close fit between the stoma bag and the skin. This helps prevent excrement leakage, keeps the skin dry, and protects the viscose of the stoma bag from erosion, thereby improving the use effect.

[0003] In the related art, the types of leak-proof ointments are mainly alcohol-containing and alcohol-free. Alcohol-containing leak-proof ointments contain alcohol, while alcohol-free leak-proof ointments do not contain alcohol. Although alcohol-containing leak-proof ointments are easy to extrude, they have the defect of poor corrosion resistance of the ointment and cannot protect the ostomy bag. Moreover, they are mostly made of polyvinyl pyrrolidone and povidone iodine. The solubility of alcohol is greatly affected by temperature. The thermal stability of the product is poor and phase separation is prone to occur. Alcohol-containing leak-proof ointments are still sticky after the ointment is extruded, causing inconvenience during plasticization. At the same time, alcohol-containing leak-proof ointments are in long-term contact with excrement and are easily swollen and disintegrated due to immersion in intestinal fluid or urine, thus losing their leak-proof effect. Although alcohol-free leak-proof ointments are less irritating to the skin, they are mostly composed of liquid rubber and have poor fluidity. In order to improve their corrosion resistance, inorganic clay is usually used as a filler, which also makes the support of the ointment slightly insufficient. Summary of the invention

[0004] The purpose of the present invention is to provide an alcohol-containing anti-leakage ointment and a preparation method and application thereof, so as to solve the problems existing in the related technology at least to a certain extent, such as solving the problems of poor corrosion resistance, insufficient support, strong skin irritation or inconvenient shaping of the existing anti-leakage ointment.

[0005] The first aspect of the present invention provides an alcohol-containing anti-leakage ointment, which comprises the following raw materials in weight percentage:

[0006] PVM / MA copolymer butyl ester 20%-40%;

[0007] Alcohol 25%-45%;

[0008] Guar gum 5%-25%;

[0009] First thickener 1%-10%;

[0010] Second thickener 3%-5%;

[0011] The first thickener is a polysaccharide substance that can form a gel with sodium ions, potassium ions or calcium ions, and the second thickener is a cellulose ether substance.

[0012] The second aspect of the present invention provides a method for preparing an alcohol-containing anti-leakage ointment, which comprises the following steps:

[0013] The PVM / MA copolymer butyl ester, guar gum, the first thickener and the second thickener are uniformly mixed, alcohol is added, and the mixture is stirred at a temperature below 40° C. for 20-120 minutes to obtain an alcohol-containing anti-leakage ointment.

[0014] A third aspect of the present invention provides the use of an alcohol-containing anti-leakage ointment in the placement of a stoma device, wherein when the stoma device is placed, the alcohol-containing anti-leakage ointment is applied between the skin and the stoma device.

[0015] It is to be understood that the contents described in this section are not intended to identify the key or important features of the embodiments of the present invention, nor are they intended to limit the scope of the present invention. Other features of the present invention will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 These are photos of the thermal stability test results of the anti-leakage paste samples of Examples 1 to 6 of the present invention, wherein numbers 1 to 6 correspond to the anti-leakage paste samples of Examples 1 to 6, respectively.

[0017] Figure 2 These are photos of the thermal stability test results of the anti-leakage ointment samples of Comparative Examples 1 to 4, wherein numbers 7 to 10 correspond to the anti-leakage ointment samples of Comparative Examples 1 to 4, respectively. DETAILED DESCRIPTION

[0018] The first aspect of the present invention provides an alcohol-containing anti-leakage ointment, which comprises the following raw materials in weight percentage:

[0019] PVM / MA copolymer butyl ester 20%-40%;

[0020] Alcohol 25%-45%;

[0021] Guar gum 5%-25%;

[0022] First thickener 1%-10%;

[0023] Second thickener 3%-5%;

[0024] The first thickener is a polysaccharide substance that can form a gel with sodium ions, potassium ions or calcium ions, and the second thickener is a cellulose ether substance.

[0025] It is understood that PVM / MA copolymer butyl ester is also known as vinyl methyl ether / maleic anhydride copolymer butyl ester, and its CAS number is 53200-28-5. Alcohol is also known as ethanol, and its structural formula is CH3CH2OH. Guar gum is also known as guar gum, which can be obtained by hydrolyzing the endosperm of guar beans (Cyamopsis tetragonoloba).

[0026] With PVM / MA copolymer butyl ester as the alcohol thickener, the alcohol on the surface of the leak-proof cream will evaporate after extrusion to form a thin film, which can build a barrier between the skin and the alcohol and reduce the irritation of alcohol to the skin; and the surface of the cream will become smooth and non-sticky after the alcohol evaporates, making it easy to shape. Alcohol in the leak-proof cream has good thermal stability, making the cream more stable. The first thickener can cross-link with sodium, potassium, calcium and other ions in the excrement to form a gel, so that the cream will not collapse and increase the strength of the cream. Guar gum, the first thickener and the second thickener have a strong cross-linking effect, and the three or two of them can form a dense polymer matrix, which increases the hardness of the cream and improves its supporting performance and corrosion resistance.

[0027] The amount of each component raw material will affect the performance of the alcohol-containing anti-leakage paste. For example, excessive use of PVM / MA copolymer butyl ester will lead to poor support performance, while too little use will lead to poor fluidity and corrosion resistance. Excessive use of ethanol will reduce the cohesion of PVN / MA copolymer butyl ester and reduce the binding force on the thickener, resulting in a decrease in the support of the paste. In addition, it takes more time for the excess ethanol to evaporate, affecting the user experience. Too little ethanol will cause the product to have a thicker consistency and strong viscosity, making it difficult to squeeze out of the tube during use. An inappropriate ratio of guar gum, the first thickener, and the second thickener will result in poor cross-linking effect and reduced support and corrosion resistance.

[0028] In some embodiments, the alcohol-containing anti-leakage ointment includes the following raw materials in weight percentage:

[0029] PVM / MA copolymer butyl ester 30%-40%;

[0030] Alcohol 30%-40%;

[0031] Guar gum 20%-25%;

[0032] First thickener 4%-7%;

[0033] Second thickener 3%-5%.

[0034] Preferably, the alcohol-containing anti-leakage ointment comprises the following raw materials in percentage by weight:

[0035] PVM / MA copolymer butyl ester 35%;

[0036] Alcohol 35%;

[0037] Guar gum 20%;

[0038] First thickener 7%;

[0039] Second thickener 3%.

[0040] In some embodiments, the first thickener is at least one of alginic acid and chitosan. Preferably, the first thickener is alginic acid.

[0041] In some embodiments, the second thickener is at least one of hydroxypropyl methylcellulose, carboxymethyl cellulose, and hydroxypropyl cellulose. Preferably, the second thickener is hydroxypropyl methylcellulose.

[0042] The second aspect of the present invention provides a method for preparing an alcohol-containing anti-leakage ointment, which comprises the following steps:

[0043] The PVM / MA copolymer butyl ester, guar gum, the first thickener and the second thickener are uniformly mixed, alcohol is added, and the mixture is stirred at a temperature below 40° C. for 20-120 minutes to obtain an alcohol-containing anti-leakage ointment.

[0044] In some embodiments, stirring is carried out at 30°C for 30 minutes.

[0045] A third aspect of the present invention provides the use of an alcohol-containing anti-leakage ointment in the placement of a stoma device, wherein when the stoma device is placed, the alcohol-containing anti-leakage ointment is applied between the skin and the stoma device.

[0046] In some embodiments, the ostomy device is an ostomy bag.

[0047] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0048] In the following examples and comparative examples, all the raw materials used can be obtained through commercial channels. Among them, the purity of ethanol is ≥99.5%.

[0049] Example 1

[0050] 350 g of PVM / MA copolymer butyl ester, 70 g of alginic acid, 30 g of hydroxypropyl methylcellulose and 200 g of guar gum were mixed evenly, and the evenly mixed powder was added into a planetary mixer, and 350 g of ethanol was added. The temperature was controlled below 40° C. and stirred for 30 minutes to obtain an alcohol-containing leak-proof ointment.

[0051] Example 2

[0052] 350 g of PVM / MA copolymer butyl ester, 100 g of alginic acid and 200 g of guar gum were mixed evenly, and the evenly mixed powder was added into a planetary mixer, and 350 g of ethanol was added. The temperature was controlled below 40° C. and stirred for 30 minutes to obtain an alcohol-containing leak-proof paste.

[0053] Example 3

[0054] 400 g of PVM / MA copolymer butyl ester, 50 g of hydroxypropyl methylcellulose and 200 g of guar gum were mixed evenly, and the evenly mixed powder was added into a planetary mixer, and 350 g of ethanol was added. The temperature was controlled below 40° C. and stirred for 30 minutes to obtain an alcohol-containing anti-leakage ointment.

[0055] Example 4

[0056] 550 g of PVM / MA copolymer butyl ester, 40 g of alginic acid and 60 g of hydroxypropyl methylcellulose were mixed evenly, and the evenly mixed powder was added into a planetary mixer, and 350 g of ethanol was added. The temperature was controlled below 40° C. and stirred for 30 minutes to obtain an alcohol-containing anti-leakage ointment.

[0057] Example 5

[0058] 600 g of PVM / MA copolymer butyl ester, 70 g of alginate, 30 g of hydroxypropyl methylcellulose and 200 g of guar gum were mixed evenly, and the evenly mixed powder was added into a planetary mixer, and 100 g of ethanol was added. The temperature was controlled below 40° C. and stirred for 30 minutes to obtain an alcohol-containing leak-proof ointment.

[0059] Example 6

[0060] 100 g of PVM / MA copolymer butyl ester, 100 g of alginate, 200 g of hydroxypropyl methylcellulose and 200 g of guar gum were mixed evenly, and the evenly mixed powder was added into a planetary mixer, and 400 g of ethanol was added. The temperature was controlled below 40° C. and stirred for 30 minutes to obtain an alcohol-containing anti-leakage ointment.

[0061] Comparative Example 1

[0062] 350 g of PVM / MA copolymer butyl ester, 70 g of alginate, 30 g of polyvinyl pyrrolidone and 200 g of guar gum were mixed evenly, and the evenly mixed powder was added into a planetary mixer, and 350 g of ethanol was added. The temperature was controlled below 40° C. and stirred for 30 minutes to obtain an alcohol-containing anti-leakage ointment.

[0063] Comparative Example 2

[0064] 350 g of PVM / MA copolymer butyl ester, 70 g of alginic acid, 30 g of hydroxypropyl methylcellulose and 200 g of inorganic clay were mixed evenly, and the evenly mixed powder was added into a planetary mixer, and 350 g of ethanol was added. The temperature was controlled below 40° C. and stirred for 30 minutes to obtain an alcohol-containing anti-leakage ointment.

[0065] Comparative Example 3

[0066] 350 g of PVM / MA copolymer butyl ester, 70 g of alginate, 30 g of hydroxypropyl methylcellulose and 200 g of guar gum were mixed evenly, and the evenly mixed powder was added into a planetary mixer, and 350 g of butanol was added. The temperature was controlled below 40° C. and stirred for 30 minutes to obtain a butanol-containing anti-leakage paste.

[0067] Comparative Example 4

[0068] 350 g of PVM / MA copolymer butyl ester, 70 g of alginic acid, 30 g of hydroxypropyl methylcellulose and 200 g of guar gum were mixed evenly, and the evenly mixed powder was added into a planetary mixer, and 350 g of water was added. The temperature was controlled below 40° C. and stirred for 30 minutes to obtain an alcohol-free anti-leakage ointment.

[0069] Table 1 Weight percentage of raw materials in Example 1-Example 6, Comparative Example 1-Comparative Example 4

[0070]

[0071]

[0072] The products of Examples 1 to 6 and Comparative Examples 1 to 4 were sampled and packaged into aluminum-plastic tubes by a canning and sealing machine. The surface drying time, thermal stability, support and corrosion resistance of the samples were tested. The test results are shown in Tables 2 and Figure 1-Figure 2 shown.

[0073] The test method for surface drying time is: squeeze out 20mm of the sample and discard it, then squeeze out 30mm on the release surface of the release paper, and use a stopwatch to record the time when the hand touches the paste without sticking.

[0074] The test method for thermal stability is: seal 60g of sample in an aluminum-plastic tube, place in an oven at 60°C for 7 days, open the aluminum-plastic tube and squeeze out the paste, and observe the morphology of the paste.

[0075] The test method for support is as follows: take two clean glass plates of 20cm×20cm in size, the upper glass plate weighs 500g (if the weight is insufficient, add weights to make up for it), and use tape to stick a transparent area measuring device (purchased from the Taobao store of Kuhui Crafts Factory, with a length and width of 120mm×120mm) to the middle of the lower glass plate for later use; take 3 test samples, first squeeze out 20mm of the sample and discard it; continue to squeeze out the sample, weigh 0.5g±0.01g 3 times in succession, and place it between the two glass plates. Note that each time the paste should be squeezed into 4 small squares (0.5cm×0.5cm) in the lower glass plate, and record the increased area of ​​the paste after extension after 10 minutes (the smaller the area, the better the support), and record 0.25cm if it exceeds half of the grid. 2 , if it is less than half, record it as 0.

[0076] The test method for corrosion resistance is as follows: squeeze out 20 mm of the sample and discard it, take about 5 g and place it in a 250 ml conical flask, accurately weigh the sample mass M1 and the total weight of the sample and the conical flask M2; put a certain amount of artificial small intestinal fluid into the conical flask containing the sample, just enough to cover the surface of the sample, and seal the bottle mouth with a stopper; put the sealed conical flask in a 37°C constant temperature incubator, take out the conical flask after 18 hours, pour out the remaining liquid in the bottle, place the remaining paste in the bottle in a 60°C oven to dry, take it out after 16 hours, and weigh the weight of the sample and the conical flask M3 at this time; corrosion resistance = {1-(M2-M3) / M1}×100%.

[0077] Table 2 Sample test results

[0078]

[0079]

[0080] From Table 2 and Figure 1-Figure 2It can be seen that compared with Examples 2 to 4, the alginate, hydroxypropyl methylcellulose and guar gum of Example 1 construct a stable system in the paste, which greatly improves its support and corrosion resistance. Example 5 uses more PVM / MA copolymer butyl ester, resulting in an unstable paste state, so the support is poor; and the surface will become smooth after a long period of time after extrusion, affecting the patient's use. Example 6 uses less PVM / MA copolymer butyl ester, resulting in poor paste fluidity; and lacks the protection of the film formed by PVM / MA copolymer butyl ester, and the corrosion resistance is also reduced. Comparative Example 1 replaces PVM / MA copolymer butyl ester with polyvinyl pyrrolidone, and the paste undergoes phase separation after heating; similar to Example 6, lacks the protection of the film formed by PVM / MA copolymer butyl ester, and the corrosion resistance is poor. Comparative Example 2 uses inorganic clay as a filler for the paste, and the paste support and corrosion resistance are slightly insufficient. Comparative Example 3 uses butanol as a solvent. After the paste is extruded, the solvent evaporates slowly, resulting in a sticky surface of the paste, affecting the use experience. Comparative Example 4 uses water as a solvent. After extrusion, the water on the surface of the paste is extremely difficult to evaporate, and the paste has no continuity and no corrosion resistance.

[0081] In addition, 60 stoma patients were recruited to conduct clinical evaluation of the anti-leakage ointment. The 60 stoma patients were evenly divided into three groups, the first group used the alcohol-containing anti-leakage ointment of Example 1 of the present invention, the second group used the alcohol-containing anti-leakage ointment of Comparative Example 1, and the third group used the alcohol-containing anti-leakage ointment of Comparative Example 2. After 15 days of use, 2 cases of leakage occurred in the first group, and 1 case of red spots on the skin; 6 cases of leakage occurred in the second group, and 5 cases of red spots on the skin; 4 cases of leakage occurred in the third group, and 2 cases of red spots on the skin. The clinical evaluation results show that the alcohol-containing anti-leakage ointment of Example 1 of the present invention has a good anti-leakage effect and weak skin irritation.

[0082] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An alcohol-containing anti-leakage ointment, characterized in that: The following raw materials are included in weight percentage: PVM / MA copolymer butyl ester 20%-40%; Alcohol 25%-45%; Guar gum 5%-25%; First thickener 1%-10%; Second thickener 3%-5%; The first thickener is a polysaccharide substance that can form a gel with sodium ions, potassium ions or calcium ions, and the second thickener is a cellulose ether substance.

2. The alcohol-containing anti-leakage ointment according to claim 1, characterized in that: The invention comprises the following raw materials in weight percentage: 30%-40% of PVM / MA copolymer butyl ester; Alcohol 30%-40%; Guar gum 20%-25%; First thickener 4%-7%; Second thickener 3%-5%.

3. The alcohol-containing anti-leakage ointment according to claim 2, characterized in that: The invention comprises the following raw materials in weight percentage: 35% of PVM / MA copolymer butyl ester; Alcohol 35%; Guar gum 20%; First thickener 7%; Second thickener 3%.

4. The alcohol-containing anti-leakage ointment according to claim 1, characterized in that: The first thickener is at least one of alginic acid and chitosan.

5. The alcohol-containing anti-leakage ointment according to claim 4, characterized in that: The first thickener is alginic acid.

6. The alcohol-containing anti-leakage ointment according to claim 1, characterized in that: The second thickener is at least one of hydroxypropyl methylcellulose, carboxymethyl cellulose and hydroxypropyl cellulose.

7. The alcohol-containing anti-leakage ointment according to claim 6, characterized in that: The secondary thickener is hydroxypropyl methylcellulose.

8. The method for preparing the alcohol-containing anti-leakage ointment according to any one of claims 1 to 7, characterized in that: The following steps are involved: The PVM / MA copolymer butyl ester, guar gum, the first thickener and the second thickener are uniformly mixed, alcohol is added, and the mixture is stirred at a temperature below 40° C. for 20-120 minutes to obtain an alcohol-containing anti-leakage ointment.

9. Use of the alcohol-containing anti-leakage paste according to claim 1 in arranging a stoma device, wherein: When placing the stoma device, apply an alcohol-based leak-proof ointment between the skin and the stoma device.

10. The use according to claim 9, characterized in that: The stoma device is a stoma bag.